THE USE OF EDMODO IN TEACHING WRITING PROCEDURE TEXT FOR THE ELEVENTH GRADE OF VOCATIONAL HIGH SCHOOL - Br. Harahap, Nur Anisyah; Pulungan, Anni Holila; Hartoyo, Indra (Universitas Negeri Medan, 2019)
This study was about the use of Edmodo in teaching writing procedue text, to invstigate the problems when using Edmodo in teaching of writing text, and to find out the use of Edmodo and the problems. The participants of this research was English Teacher and Students of XI-TKJ 1 class of SMKN 2 Binjai. The technique of data collection used was observation and interview. The research finding Edmodo media showed that there twelve steps how to use of Edmodo that were used; (1) Teacher Sign Up, (2) Students Sign Up, (3) Basic Posting, (4) Posting Alert, (5)Posting Polls, (6) Working with Assigments, (7) Creating a Quiz, (8) Assigning Quiz, (9) Taking the Quiz, (10) Grades, (11) Calender and Library, (12) and Feeds. Moreover, here were two problems faced in using Edmodo in teaching writing procedure text; (1)The problems from teachers (2) The problems from studentsKeywords: Edmodo, Writing, Procedue Text.